A Wedding Toast Is Not a State of the Union Address: Other-Regarding and Others’ Opinions Regarding Preferences As Relevant Factors in Shaping Human Preferences - Warren, Jerome Nikolai (ETHICS IN PROGRESS, 2015)
This paper describes using current literature and research a problem that has plagued social scientists for centuries, see that of „moral sentiments?. Human beings are inherently social by nature and hold certain regard for others? opinions (esteem preferences) as well as for others generally (altruism). It is argued in the article that such preferences may in fact be consistent with a core rational human agent. It is furthermore argued that the lack of regard for such preferences in social sciences research (and particularly within the domain of economics) severely weakens models and theories in the respective disciplines. A few potential avenues for including social preferences writ large into social science (read: economic) modeling are outlined.